Development of a three-directional vibration isolator for buildings subject to metro- and earthquake-induced vibrations - Sheng, Tao; Liu, Gan-bin; Bian, Xue-cheng; Shi, Wei-xing; Chen, Yue (Engineering structures, 2022)
•A vibration isolator is developed to suppress metro- and earthquake-induced building vibrations.•The mechanical properties of the new isolator are investigated by pseudo-static tests.•Suppression effectiveness for vertical metro vibrations is verified by field experiments.•Suppression effectiveness for horizontal seismic vibrations is verified by numerical analyses. In this paper, a new three-directional vibration isolator for buildings was developed to suppress vertical metro vibrations and horizontal seismic vibrations simultaneously. The isolator was a laminated rubber bearing (LRB) with vertical through-holes. The holes were filled with a mixture of sand and rubber particles. The pseudo-static testing results show that the compression stiffness of the new isolator is relatively smaller than that of the traditional LRB and that the stiffness can be easily adjusted. The vertical damping ratio reached 9%. These advantages are appropriate for suppressing vertical metro vibrations. Because of the frictional forces of the particle mixture, the horizontal damping ratio reached 24%, and the shear stiffness dependencies were similar to those of traditional LRBs. The ultimate shear strain reached 350%. Therefore, the isolator’s horizontal seismic isolation performance was similar to those of high-damping LRBs. By applying viscous damping forces to simulate frictional forces, a finite element (FE) model is proposed for the new isolator. The model can efficiently analyze the mechanical properties. To investigate the feasibility of the new isolator, field experiments were carried out using a full-scale masonry building adjacent to a metro line. The results show that the metro-induced vertical vibrations and vibration-induced noises were significantly suppressed after the installation of the new isolators. Finally, numerical analyses of the seismic isolation performance were carried out using a six-story building under rare earthquakes. The results show that no tensile stress occurred on the new isolators and both the compressive stress and shear strain were less than the bearing capacity. Therefore, the new isolator is feasible for buildings subject to metro- and earthquake-induced vibrations.